Effect of Duration of Seed Soaking before Sowing on Mungbean under Rainfed Conditions in the Southern Region of Bangladesh - Razzaque, MA; Rafiquzzaman, S; Islam, MN (Journal of Agriculture & Rural Development, 2008)
A field experiment was conducted at the farming system research and development site Lebukhali, Patuakhali of Bangladesh Agricultural Research Institute during 1999 and 2000 to study the effect of seed soaking duration before sowing on yield of two mungbean varieties BARImung-2 and BARImung-5. Seeds were soaked with fresh water for 0, 2, 4, 6 and 8 hours. The results revealed that plants produced with 4 hours soaking gave the maximum seed yield (1379 kg/ha). BARImung-5 produced higher yield (1457 kg/ha) than that of BARImung 2. Control (no soaking) gave lower yield. The highest benefit cost ratio (3.51) was obtained from 4 hours soaking. Key words: Mungbean variety, time of seed soaking, yield.